Validation of DSCOVR-EPIC total column O3 retrievals using ground-based Pandora as well as OMPS, OMI, and TEMPO satellite data - Herman, Jay; Mao, Jianping; Huang, Liang; Cede, Alexander (Frontiers in Remote Sensing, 2025)
The Earth polychromatic imaging camera (EPIC) onboard the deep space climate observatory (DSCOVR) began obtaining fully illuminated Earth images across 10 wavelength bands on 6 July 2015. The ultraviolet bands 317, 325, 340, and 388 nm are used to retrieve the total column ozone (TCO) values at different local times during the day. On 28 June 2019, the spacecraft experienced a gyroscope failure; after recovery, the EPIC TCO values retrieved from 2021 to 2024 still agree well with those obtained from the ground-based Pandora spectrometer instruments in terms of both the hourly and weekly average basis. The hourly EPIC TCO values show more variability than the matched Pandora TCO values but generally deviate within 2% while tracking the shape of the Pandora daily variations in most cases. At 13:30 hours, the TCO data from the ozone and mapping profiler suite (OMPS) and ozone monitoring instrument (OMI) are also observed to frequently agree with the time-matched Pandora and EPIC TCO values. In addition, comparisons were made with the version-3 (V03) hourly TCO retrievals from the US tropospheric monitoring of pollution (TEMPO) geostationary satellite over two North American sites, namely, Toronto (Canada) and Dearborn (Michigan, United States). The long-term weekly lowess average EPIC and Pandora TCO values agree with deviations of less than 2%, as does the 3-week lowess average of the OMPS TCO value. An analysis of the TCO values from Pandora and 1 year of TEMPO V03 suggests that the noon TCO values are 2%–5% higher than the morning and afternoon values.